Language learning motivation and gender: The case of Poland. (20th February 2019) - Iwaniec, Janina
Abstract : Gender differences in language learning motivation have not been extensively examined. Thus, this survey study explores gender differences in the population of 599 Polish learners of English aged 14–16. Unlike other studies, it not only compares means but investigates whether there are gender differences in the way the variables interact with each other. Findings show that females scored higher than males on scales of international orientation, ideal L2 self and self‐regulation. No gender differences were observed on instrumentality, self‐efficacy beliefs, English self‐concept and intrinsic motivation. There is also a significant difference in the strength of links between self‐regulation and instrumentality, self‐efficacy beliefs as well as English self‐concept. Thus, gender effects appear more extensive than previous research has shown.